2008
DOI: 10.1007/s11605-007-0397-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laparoscopic Fundoplication on Hypertensive Lower Esophageal Sphincter Associated with Gastroesophageal Reflux

Abstract: For hypertensive lower esophageal sphincter with dysphagia and chest pain, a laparoscopic cardiomyotomy is recommended. Recently, the role of gastroesophageal reflux in this abnormality has been recognized. A prospective study on six patients with manometrically proven hypertensive lower esophageal sphincter was performed. Laparoscopic floppy Nissen fundoplication was performed in all cases. The first follow up was performed 6 weeks after the operation. The mean follow up time was 56 months (range 50-61). Befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Some of these patients can benefit from surgery. Varga et al reported a series of patients with HLES, who were submitted to a floppy NF: mean LES pressure changed six weeks after surgery from 50.5 mm Hg to 24.7 mm Hg, and 15.7 mm Hg at late follow‐up, and no cases of postsurgery dysphagia were reported in this group of patients 19 …”
Section: What Is the Effect Of The Various Ar Procedures On The Les?mentioning
confidence: 77%
See 1 more Smart Citation
“…Some of these patients can benefit from surgery. Varga et al reported a series of patients with HLES, who were submitted to a floppy NF: mean LES pressure changed six weeks after surgery from 50.5 mm Hg to 24.7 mm Hg, and 15.7 mm Hg at late follow‐up, and no cases of postsurgery dysphagia were reported in this group of patients 19 …”
Section: What Is the Effect Of The Various Ar Procedures On The Les?mentioning
confidence: 77%
“…Varga et al reported a series of patients with HLES, who were submitted to a floppy NF: mean LES pressure changed six weeks after surgery from 50.5 mm Hg to 24.7 mm Hg, and 15.7 mm Hg at late follow-up, and no cases of postsurgery dysphagia were reported in this group of patients. 19 Besides, abnormality of the LES pressure profile after fundoplication can be determined by an anatomical failure of the wrap (e.g., intrathoracic migration): for example, the recognition of a dual high-pressure zone (HPZ) at HRM correlates with recurrent hiatal hernia. 20 In conclusion, numerous studies have shown that surgical procedures lead to a significant postoperative improvement of manometric parameters of LES, mainly in patients with severe GERD (erosive disease or BE); further studies may help to predict the outcome of surgical treatment in patients with NERD.…”
Section: What Is the Effect Of The Various Ar Procedures On The Les?mentioning
confidence: 99%
“…However, it is worth noting that no patient has undergone a myotomy for dysphagia and an isolated hypertensive LES, since the laparoscopic approach was introduced to the unit in 1992. Small studies have previously reported encouraging results after fundoplication in patients with reflux and a hypertensive LES, with good outcomes for 11 of 12 patients, 3 six of six patients, 5 and three of four patients, 14 respectively. In our study, the long-term outcome was encouraging, with a significant reduction in heartburn symptoms and high levels of patient satisfaction, similar to a matched control group.…”
Section: Discussionmentioning
confidence: 97%
“…2 However, most published studies evaluating the condition have used less stringent criteria and a lower cutoff, between 26 and 35 mm Hg, mid respiration. [3][4][5] Chest pain and dysphagia were initially reported to be the most common symptoms associated with a hypertensive LES, and treatment was directed at reducing sphincter pressure, by medical or surgical techniques. 6,7 Although some patients fit this algorithm, it is now recognized that there is another group who present primarily with heartburn and are proven to have gastroesophageal reflux.…”
Section: Introductionmentioning
confidence: 99%
“…The main evidence for hypertensive LES being secondary to acid reflux is the fact that following a Nissen fundoplication sphincter pressure, and pH-metry, values get in the normal range again and reflux symptoms disappear. 18 , 19 A further protective mechanism to reduce excessive acid exposure of the esophagus is the development of a lower esophageal or Schatzki’s ring. GERD has been reported to be present in 31%–60% of the cases, with hiatal hernia reported to be a cofinding in all patients with Schatzki’s ring.…”
Section: Discussionmentioning
confidence: 99%